Determination and stability testing method of chlorpheniramine maleate in the presence of tartrazine using HPLC - Asri Darmawati; Febri Annuryanti; Riesta Primaharinastiti; Isnaeni Isnaeni (Pharmaciana, 2020)
The single-component CPM tablet mostly used sodium tartrazine as the yellow coloring agent. Sodium tartrazine is soluble in solvents used to extract CPM from tablet and suspected interference CPM determination especially after forced degradation for stability indication testing of CPM tablets. This study aimed to develop a selective, accurate and precise method for determination and stability testing of chlorpheniramine maleate (CPM) in the presence of tartrazine in the tablet. A µBondapak® C18 column (3.9 x 300 mm, 10 µm) with diode array detector was used for separation. The mobile phase was a mixture of methanol and 0.2% triethylamine (90:10) with a flow rate of 2 mL/minutes. The validated HPLC method was used for CPM determination in tablet samples that had been forced degraded using dry heat at 105oC, UV radiation of 254 nm, hydrolysis with 1N NaOH, 1N HCl and oxidation using 5% H2O2. The HPLC chromatogram showed that CPM split into chlorpheniramine (CP) and maleic acid (MA). Resolution (Rs) among CP and the other analytes especially with the products resulting from the forced degradation by heat, UV radiation, HCl, and H2O2 were good. The CPM hydrolysis using NaOH caused the CP not completely separated from the degradation product due to tailing or overlapping peaks. The proposed HPLC method was valid for the determination of CPM in tablets containing tartrazine. Even though the stability-indicating method was inadequate especially for the result of the CPM hydrolysis process using NaOH.